Capitol women : Texas female legislators, 1923-1999 - Jones, Nancy Baker (University of Texas Press, 2000)
"Capitol Women, brings together for the first time the stories of Texas's women legislators. Through biographies, photographs, and interviews, this book captures their lives, campaign strategies, and legislative struggles and successes."--Jacket.